The role of job crafting in the relationship between job resources and exhaustion among teachers - Lazauskaitė-Zabielskė, Jurgita; Urbanavičiūtė, Ieva; Rekašiūtė Balsienė, Rita (Psichologija, 2018)
Exhaustion at work is defined as a state of intensive physical, emotional and cognitive strain (Demerouti et al., 2001). Being related to physical and psychological health impairment (Hakkanen & Schaufeli, 2012), lower performance (Bakker & Heuven, 2006; Taris, 2006) and turnover (Schaufeli, Bakker, & Van Rhenen, 2009), its antecedents have widely attracted researchers’ attention. One of the most prominent theoretical frameworks for analyzing exhaustion is the Job Demands-Resources Model, which is developed by Bakker and Demerouti (2007; 2014). The model states that it’s the disbalance betweeb job demands and job resources that lead to higher levels of exhaustion. Not surprisingly, most of the interventions are aimed at increasng job resources (Leiter & Maslach, 2014). Moreover, lately, the proactive role of the employee (i. e., job crafting) in shaping his/her working environment has been recognized (Tims & Bakker, 2010; Wrzesniewski & Dutton, 2001). However, the empirical data on the interaction between job resources and job crafting is still lacking. Therefore, the study was conducted with the aim to determine the role of job crafting in the relationship betweeb job resources and exhaustion. A total of 341 teachers from various state schools in Lithuania were surveyed. Ninety two percent of the respondents were female, eight percent were male. The average age of respondents was 46.36 (SD = 10.64) years, with the average of 23.59 (SD = 11.16) years of working experience. Most of the respondents (85%) had higher education. The analysis revealed job crafting to moderate the relationship between job resources and exhaustion. More precisely, job resources were negatively related to exhaustion when employees engaged in particular job crafting strategies. The results of the study showed that autonomy, the opportunity to develop and social support were related to lower exhaustion only when the teachers had increased structural job resources, that is, when they tried to use their capacities to the fullest in developing professionally and learning new things at work. Moreoever, autonomy and social support negatively predicted exhaustion when employees aimed at increasing challenging demands. In other words, flexibility in the planning and execution of one’s job and being able to ask colleagues for help and support was related to lower levels of exhaustion only when teachers regularly took on extra tasks, tried to make their work more challenging and proactively offered themselves for interesting projects. In general, the results of the study highlight the importance of the proactive behavior of employees in using job resources to diminish exhaustion.